The Niger Basin Authority has integrated Nexus Indicators into its operational and investment planning until 2024, covering 350 projects - CGIAR Research Program on Water, Land and Ecosystems (2021)
The Niger Basin Authority Operational Plan 2016-2024 includes 350 projects. To ensure they advance the Shared Vision of the Niger Basin, a Nexus perspective that simultaneously considers synergies and tradeoffs across water, energy and food security and environmental sustainability is essential. The Nexus Regional Dialogue Program supported analysis of the Operational Plan through a Nexus perspective and development of a Nexus framework. The Niger Basin Authority has agreed to incorporate this into its 2022 Operational Plan exercise.